Strength Analysis of Tubular Oil to Oil Cable Box Power Transformer GIS 60 MVA in the Case of Voltage Arc Energy Using the Finite Element Analysis Method - Wilarso Wilarso; Asep Dharmanto; Asep Saepudin (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
The power transformer is an essential part of the electrical distribution system because it must be reliable and safe from fire and explosions, one of which is brought on by internal oil arching that results in overheating. In general, on the high voltage side of the transformer, there are power transformers fitted with tubular oil to oil cable boxes for the demands of the client. The tubular oil to oil cable box is installed to reduce space in substations with limited space as well as to boost safety against weather and pollution at the high voltage terminal section of power transformers. The goal of this investigation is to determine the cause of an explosion that occurred in a tubular oil-to-oil cable box on the high voltage side of a Gas Insulation System (GIS) type power transformer with a power of 60 MVA and a voltage rating of 150/20 kV. For all parties involved, this incident will serve as a lesson about what to avoid doing in the future with similar power transformers. In this study, we will use a qualitative method with Finite Element Analysis (FEA), which takes samples and data of a Gas Insulation System (GIS) power transformer on the high voltage side, especially in the analysis of tubular strength. This power transformer has a voltage rating of 150/20 kV and a power of 60 MVA. Applying normal pressure to a pressure that could harm the tubular oil to oil cable box can prevent damage. The tubular oil to oil cable box is built of SS400 material and has an 8mm thickness so that it can be determined how robust it is.